Axel Elof Jäderholm (1868–1927) of Sweden: educator, hydrozoan zoologist and botanist. Issue 2 (October 2014) - Calder, Dale R.
Abstract : Axel Elof Jäderholm was born in Söderhamn, Sweden, on 24 July 1868. In 1888 he entered Uppsala Universitet, earning undergraduate (1892) and doctorate (1898) degrees. His doctoral dissertation was based on an anatomical study of South American Peperomia (Piperaceae). While a graduate student he commenced research on hydroids in collections at the university's natural history museum. A science teacher by profession, he served schools in Uppsala (1900–1901), Norrköping (1901–1905; 1913–1927), Örebro (1905) and Västervik (1905–1913). In addition to teaching, he undertook research in botany (especially mosses) and zoology (hydroids). A focus of work between 1903 and 1905 involved examination of hydroid collections at the Naturhistoriska Riksmuseet (Stockholm) and the Imperial St Petersburg Academy of Sciences (Russia). Jäderholm's field work dealt largely with bryophytes, although his scientific publications (21 of 28) were mostly on taxonomy of hydroids. His hydroid work was mainly on species from northern Europe, the Antarctic and sub-Antarctic, southern regions of South America, and the western Pacific (especially Japan). He established two new genera and 69 new species of hydroids, a majority of the latter still being recognized as valid. Jäderholm was created a knight of the Order of the Polar Star (Riddare av Nordstjärneorden) in Sweden for accomplishments in science and education. After suffering a series of acute illnesses over the last two years of his life, he died in Norrköping on 5 March 1927 and was buried in Uppsala. Five species of hydroids have been named in his honour.